Coping Strategies And Stress Management: Managers’ Experiences With The ’Art Of Living’ In Singapore - Retna, Kala (School of Management Working Papers, 2011)
Studies have identified stress as a central factor that shaping the well-being of employees and organisational performance. As a result many organisations have implemented stress management programmes to enable employees to cope with and reduce stress. However, despite efforts and investment in stress intervention programmes, there is little literature that examines the benefits and impacts of the stress management coping strategies for employees. Using qualitative research methodology, this study examines a sample of working professionals who had attended a specific stress management programme run by the Art of Living (AOL) foundation in Singapore. The study focuses on the „transactional‟ model (Lazarus & Folkman, 1884) that explains the negative psychological state resulting from stress. The findings highlight a preference for stress management coping strategies that can be adopted flexibly to fit the time constraints and lives of workers. The participants identify coping strategies that are helpful, but remain embedded within an organisational and societal context that is the source of stress and remains unchanged. Implications for further research are discussed.